Standpoint Suicide Attempts Dalam Film Kembang Api - Rahmansyah, Artaji; SM, Anis Endang; Dianthi, Martha Herinazwi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Suicide is a serious public health issue, with approximately 800,000 deaths each year according to the World Health Organization (WHO). In Indonesia, suicides are increasing, reaching 971 incidents by 2023. The movie